"Similar self-preservation" and decomposition kinetics of tetrahydrofuran-hydrogen hydrate particles. (12th February 2022) - Lang, Xuemei; Zheng, Caijuan; Fan, Shuanshi; Wang, Yanhong; Li, Gang; Wang, Shenglong; Yu, Chi
Abstract: Storage hydrogen using hydrates is a promising alternative to other hydrogen storage technologies. In this work, the effects of pressure and temperature on the decomposition kinetics of binary THF-H2 hydrates was investigated systematically in the pressure range of 0.1 MPa–7 MPa and temperature from 243 K to 273 K. The results showed that the dissociation of THF-H2 hydrates could be divided into three stages, rapid decomposition, slow decomposition, and stable state. The higher the pressure, the lower the dissociation rate of THF-H2 hydrates in the final stable stage. It was worth to note that the dissociation rate of THF-H2 hydrates does not show a simple linear relationship with temperature. The anomalous phenomenon of THF-H2 hydrates dissociation was observed in the temperature region of 253 K and 268 K under 5 MPa, especially at 268 K, and it was called "similar self-preservation" phenomenon. The dissociation ratio of THF-H2 hydrates in 80 h was not more than 50 mol% at 268 K and 5 MPa. This study provides practical way for developing clathrate hydrate-based storage hydrogen (transport and application) in the future. Graphical abstract: Image 1 Highlights: The "similar self-preservation effect" of THF-H2 hydrates was discovered. The self-preservation region of THF-H2 hydrates was in the range of 253 K and 268 K at 5 MPa. Less than 50% hydrogen lose from binary THF-H2 hydrates preserving at 268 K and 5 MPa after 80 h. Three-stages decomposition mechanism of binary THF-H2 hydrates was proposed.